2016
DOI: 10.1080/10790268.2016.1226701
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of energy efficiency between Wearable Power-Assist Locomotor (WPAL) and two types of knee-ankle-foot orthoses with a medial single hip joint (MSH-KAFO)

Abstract: WPAL is a practical and energy efficient type of robotics that may be used by patients with paraplegia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 20 publications
(29 reference statements)
1
17
0
Order By: Relevance
“…In particular, in the 30MWT, which is a long-distance walking test, there was a significant reduction in energy consumption without differences in distance and speed between the two groups. These results are in line with previous findings whereby RGO and WPAL had higher energy efficiencies during gait training than KAFO, with little change in PCI and HR [21,22].…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In particular, in the 30MWT, which is a long-distance walking test, there was a significant reduction in energy consumption without differences in distance and speed between the two groups. These results are in line with previous findings whereby RGO and WPAL had higher energy efficiencies during gait training than KAFO, with little change in PCI and HR [21,22].…”
Section: Discussionsupporting
confidence: 93%
“…Their results showed that gait speed and distance were better during walking with the exoskeleton robot than with KAFO braces. Moreover, energy efficiency (e.g., HR, PCI) was also higher while walking with exoskeleton robots [12,21,22].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…The metabolic cost of patients under conditions of robotic assistance is lower than without any assistance but still tremendously high compared with healthy subjects with robotic assistance. Walker-based has potential to achieve greater energy efficiency compared with other robotic aids [46]. The energy efficiency of wheeled locomotion is eight times higher than ordinary crawl gait [47], meaning that MGRRs have more potential.…”
Section: B Analysis Of Gait Rehabilitation Robotmentioning
confidence: 99%